Interaction between European Law and Private International Law: from Rome to Maastricht - Babkina, Elena V. (Journal of the Belarusian State University. International Relations, 2019)
The author demonstrates that nowadays European Union Law and Private International Law have many areas of common interests, but the process of their mutual penetration was long and gradual. The article examines Private International Law instruments adopted by the Rome Treaty of 1952 and the Maastricht Treaty of 1992, during the so-called pre-Amsterdam period. The author focuses on the role of the European Court of Justice in gradual converging of European Union Law and Private International Law.